2015
DOI: 10.1186/s12886-015-0064-5
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy versus anti-vascular endothelial growth factor agents for polypoidal choroidal vasculopathy: A meta-analysis

Abstract: BackgroundThe aim of this study was to evaluate the efficacy and tolerability of photodynamic therapy (PDT) compared to intravitreal vascular endothelial growth factor (VEGF) inhibitors in the treatment of polypoidal choroidal vasculopathy (PCV).MethodsRelevant studies were selected through an extensive search of the PubMed, EMBASE, Web of Science, and Cochrane Library databases. Outcomes of interest included visual outcomes, anatomic variables, and adverse events.ResultsSix studies enrolling a total of 346 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…; Yong et al. ). When combined, PDT reduces the need for intravitreal anti‐VEGF injections (Koh et al.…”
Section: Treatmentmentioning
confidence: 97%
“…; Yong et al. ). When combined, PDT reduces the need for intravitreal anti‐VEGF injections (Koh et al.…”
Section: Treatmentmentioning
confidence: 97%
“…25,27,32 As for intravitreal anti-VEGF injections, the rapid resolution of exudative fluid and retinal oedema can play an important role in ensuring favourable BCVA outcomes. 10 In this meta-analysis, combined therapy utilising PDT and anti-VEGF was superior to PDT in improving BCVA at all follow-up points, suggesting that anti-VEGF may overcome the deficiencies of PDT monotherapy with regard to this aspect. Furthermore, BCVA improvements seemed to decrease with time in the PDT monotherapy group, suggesting that additional PDT may be necessary to sustain these improvements.…”
Section: Discussionmentioning
confidence: 75%
“…Some studies have reported that PDT was superior to anti‐VEGF therapy in terms of polyp regression . As for intravitreal anti‐VEGF injections, the rapid resolution of exudative fluid and retinal oedema can play an important role in ensuring favourable BCVA outcomes …”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have demonstrated that PCV showed a good visual outcome with IVR [6,7,18] , but it is also known that certain PCV cases exhibited poor response to IVR [10,19] although the reasons were unknown. In the present study, type 1 PCV classified by the presence of clear BVN with polypoidal lesions showed a good visual outcome of IVR, but type 2 PCV did not show any improvement in mean BCVA.…”
Section: Discussionmentioning
confidence: 99%